Effect of gibberellic acid on reserve food mobilization of maize (Zea mays L. var Arun-2) endosperm during germination - Subedi, Chandra K; Bhattarai, Tribikram (Himalayan Journal of Sciences, 2006)
In the first 24 hrs of germination, the dry matter of the growth axis decreased in the control while in 1 mg/l GA3 solution it increased and in 10 mg/l and 100 mg/l the amount remained the same. Exogenous GA3 overcomes the dry matter loss in the growth axis during the initial stage and results in an increase in the amount of dry matter. GA3 application probably mobilized more soluble sugar to the growth axis, which results in an increase in the amount of soluble sugar in the growth axis as compared to caryopsis grown under control. 1 mg/l GA3 enhanced the amount of soluble sugar and decreased the ether extract. In protein mobilization, 1mg/l and 10mg/l GA3 solution appeared as effective as other treatments during the period from 48 to 96 hrs after sowing. The germination of seeds correlated directly with the mobilization of endosperm reserve. The seeds treated with 1 mg/l GA3 solution showed higher mobilization of endosperm reserve, which ultimately showed the higher germination percentage.Key words: GA3 mobilization, Zea mays, reserve food, protein, soluble sugar, ether extractHimalayan Journal of Sciences 1(2): 99-102, 2003